2014
DOI: 10.1007/s11427-014-4680-8
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro and in vivo anti-tumor effects of MTX-Fe3O4-PLLA-PEG-PLLA microspheres prepared by suspension-enhanced dispersion by supercritical CO2

Abstract: The in vitro and in vivo anti-tumor efficacy of methotrexate-loaded Fe 3 O 4 -poly-L-lactide-poly(ethylene glycol)-poly-L-lactide magnetic composite microspheres (MTX-Fe 3 O 4 -PLLA-PEG-PLLA MCMs, MMCMs), which were produced by co-precipitation (C) and microencapsulation (M) in a supercritical process, was evaluated at various levels: cellular, molecular, and integrated. The results at the cellular level indicate that MMCMs (M) show a better anti-proliferation activity than raw MTX and could induce morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…12, it can be observed that many dead cells existed in the group of siRNA-PTX-CMPs within 48 hours, demonstrating 85 that the CMPs based on PLLA-PEG-PLLA had entered the cells and achieved a good antitumor effect. Chen et al 47 used methotrexate-loaded PLLA-PEG-PLLA microparticles in the treatment of MG-63 cells and concluded that the drug-loaded microparticles could induce the apoptosis and death of cells, and 90 this supports the above findings. As shown in Fig.…”
Section: Antitumor Effect Of the Drug-loaded Cmpsmentioning
confidence: 74%
“…12, it can be observed that many dead cells existed in the group of siRNA-PTX-CMPs within 48 hours, demonstrating 85 that the CMPs based on PLLA-PEG-PLLA had entered the cells and achieved a good antitumor effect. Chen et al 47 used methotrexate-loaded PLLA-PEG-PLLA microparticles in the treatment of MG-63 cells and concluded that the drug-loaded microparticles could induce the apoptosis and death of cells, and 90 this supports the above findings. As shown in Fig.…”
Section: Antitumor Effect Of the Drug-loaded Cmpsmentioning
confidence: 74%
“…block copolymers such as diblock polymers(PEG-PLA) and tri-block polymers(PLA-PEG-PLA) have a wide range of effects, which can be used to increase the drug load of hydrophobic drugs, prolong blood circulation time, improve drug bioavailability and efficacy (Xiao et al, 2010;Chen et al, 2014;Ghasemi et al, 2018;Goudarzi et al, 2018;Amani et al, 2019;Girard et al, 2021;Massadeh et al, 2021). Although in vivo fate studies of triblock PLA-PEG-PLA polymers have not been reported, pharmacokinetic studies of diblock PEG-PLA polymers in rats after i.v.…”
Section: Pharmacokinetics Of Peg-plamentioning
confidence: 99%
“…[ 4a ] Moreover, traditional methods undergo a multi-step process to manufacture dosage forms. Increased demand of pharmaceutical industries in developing new approaches for drug delivery, has evidenced the SCF technology as an alternative [ 55 ] for the syntheses of micro- [ 35 , 56 ] as well as nano-size particles [ 20d,e , 57 ] with homogenous size distribution and high-performance. [ 21a ] Indeed, this technology has been used to manufacture various formulations of different drug categories such as those treating anesthesia, [ 58 ] antibiotics, [ 53 , 59 ] asthma, [ 60 ] cancer, [ 61 ] central nervous system, [ 62 ] cardiovascular system, [ 31a ] diabetes, [ 28 ] diuretics, [ 63 ] inflammation (steroidal [ 64 ] and non-steroidal anti-inflammatory agents [ 65 ] ), lipid-lowering, [ 66 ] among others, administered through oral, [ 67 ] intravenous, [ 41 ] ophthalmic, [ 68 ] pulmonary, [ 47 ] transdermal, [ 61c ] and polymeric implants for sustained delivery.…”
Section: Drug Deliverymentioning
confidence: 99%